Parametric covariance matrix modeling in Bayesian panel regression - Mickael Salabasis (Stockholm School of Economics, The Economic Research Institute (EFI), 2004)
The full Bayesian treatment of error component models typically relies on data augmentation to produce the required inference. Never stricly necessary a direct approach is always possible though not necessarily practical. The mechanics of direct sampling are outlined and a template for including model uncertainty is described. The needed tools, relying on various Markov chain Monte Carlo techniques, are developed and direct sampling, with and without effect selection, is illustrated.
Keywords: C11; C33; C63; 330; Bayesian panel regression; parametric covariance; model selection; Bayes-Statistik; Panel; Nichtparametrisches Verfahren; Theorie